Dossiers du cinéma; films 1 & 2 ; cinéastes 1 & 2. ([S.l.] : Casterman, 1971)
Marx Brothers ; Keaton, Buster ; Godard, Jean-Luc ; Hitchcock, Alfred ; Aldrich, Robert ; Antonioni, Michelangelo ; Becker, Jacques ; Carné, Marcel ; Borowczyk, Walerian ; Pétrovitch Dovjenko, Alexandre ; Flaherty, Robert ; Bertolucci, Bernardo ; Buñuel, Luis ; Clair, René ; Clément, René ; Cocteau, Jean ; De Mille, Cecil B. ; Disney, Walt ; Lang, Fritz ; Donen, Stanley ; Grémillon, Jean ; Hawks, Howard ; Polanski, Roman ; Peckinpah, Sam ; Truffaut, Francois ; Huston, John ; Lester, Richard ; Losey, Joseph ; Melville, Jean-Pierre ; Yasujiro, Ozu ; Welles, Orson ; Ray, Nicholas ; Trnka, Jirí ; Preminger, Otto ; Rouch, Jean ; Ophüls, Max ; Mankiewicz, Joseph L. ; Mann, Anthony ; Malle, Louis ; Lattuada, Alberto ; King, Henry ; Jancsó, Miklós ; Cayrol, Jean ; Borzage, Frank ; Brown, Clarence ; Munk, Andrzej
Schenking Eric de Kuyper
boek